Unleashing change a study of organizational renewal in government - Kelman, Steven (Brookings Institution Press, 2005)
"Drawing on the experience of procurement reform in the Reinventing Government initiative of the 1990s, as well as organization theory and psychology, this book presents a comprehensive approach to improving performance in big public sector organizations that addresses both theory and practice"--Provided by publisher.